The cryptogram - Mamet, David 1947- (Vintage Books, 1995)
In this gripping short play, David Mamet combines mercurial intelligence with genuinely Hitchcockian menace. The Cryptogram is a journey back into childhood and the moment of its vanishing - the moment when the sheltering world is suddenly revealed as a place full of danger. On a night in 1959 a boy is waiting to go on a camping trip with his father. His mother wants him to go to sleep. A family friend is trying to entertain them - or perhaps distract them. Because in the dark corners of this domestic scene, there are rustlings that none of the players want to hear. And out of things as innocuous as a shattered teapot and a ripped blanket, Mamet re-creates a child's terrifying discovery that the grownups are speaking in code, and that that code may never be breakable.
Keywords: Plays